2020
DOI: 10.1177/1363461520976045
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Chinese, Malay and Tamil translations of the Positive Mental Health Instrument: Cross-cultural adaptation, validity and internal consistency

Abstract: This study describes the development and validation of Chinese, Malay and Tamil translations of the Positive Mental Health Instrument (PMHI) in a general population sample in Singapore. Translations were performed using two independent forward translations followed by expert panel discussions and tested for content, construct and language appropriateness using focus group discussions. The final translated tools were field-tested among 220 residents per language using self-administered questionnaires comprising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…This study concurred with other previous translation content validity studies in Malaysia where the translation was successful and the content was acceptable [ 34 ]. This study was conducted amidst the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 90%
“…This study concurred with other previous translation content validity studies in Malaysia where the translation was successful and the content was acceptable [ 34 ]. This study was conducted amidst the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 90%
“…Although this residual value cannot be unnoticed since feeling languishing means struggling to deal with self‐growth adaptation's challenges. In sum, these students struggle to live purposeful lives (Herrero et al, 2019; Vaingankar et al, 2021) and to function well and achieve success (Demirci et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, studies of mental well-being within a unique culture such as Thailand, require sociocultural consideration. A review of past literature showed that Eastern people view social relationships as part of mental well-being ( Jiang and Ngai, 2020 ; Maulana et al., 2019 ; Vaingankar et al., 2021 ). Therefore, to accurately measure the mental well-being of the Thai population, there is a need both to develop and evaluate the reliability and validity of a new scale specific to Thai culture.…”
Section: Introductionmentioning
confidence: 99%